The Relationship Between the Role of Parents and Children's Learning Motivation During the Covid 19 Pandemic at SD IT Cahaya Hati Pauh Kambar Padang Pariaman Regency - Sidqa Adila; Wisroni Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the low learning motivation of children at SD IT Cahaya Hati Pauh Kambar, which is thought to have something to do with the role of parents in educating children. The purpose of this study was to reveal a description of the role of parents in educating children, learning motivation of children at SD IT Cahaya Hati Pauh Kambar, and to determine the relationship between the role of parents and children's learning motivation during the Covid 19 pandemic at SD IT Cahaya Hati Pauh Kambar. This type of research is a descriptive correlational study with a quantitative approach. The population of this study were all students in grade III, amounting to 100 people consisting of 4 (four) local at SD IT Cahaya Hati Pauh Kambar and a sample of 40%, namely 40 people with a sampling technique that is cluster random sampling. The data collection technique used was a questionnaire and the tools used were questionnaires. The data analysis technique uses the percentage formula and the product moment. The results of this study indicate that: 1) the role of parents in educating children is low; 2) the learning motivation of children at SD IT Cahaya Hati Pauh Kambar is low; 3) there is a significant relationship between the role of parents in educating their children and their motivation to learn at SD IT Cahaya Hati Pauh Kambar. The suggestion of this research is that it is hoped that the parents of SD IT Cahaya Hati Pauh Kambar children will further enhance their role as educators, encouragement, facilitators, and mentors while accompanying children while studying at home.